Effect on of in vitro fermentation of mixture of Tithonia diversifolia, Cenchrus clandestinum and polyunsaturated fats - Cardona Iglesias, Juan Leonardo (2017)
The aim of this study was evaluated by in vitro, the effect of mixing wild sunflower (Tithonia diversifolia), kikuyu (Cenchrus clandestinum) and concentrated feed, with the addition of polyunsaturated fatty acids (AGPI) on the production of methane (CH4 ml/g MSd), dry matter digestibility (%DIVMS) and production of volatile fatty acids (AGV). The research was conducted in NUTRILAB laboratory (Medellin, Colombia) in September 2015. Three combinations of AGPI rich lipid sources were used with a total maximum inclusion level corresponding to 3% of incubated dry matter. Combinations of lipid sources were: SAGPI1: 0.5% soya oil, 0.5% sish oil, 2% rich in omega 3 bypass fat. SAGPI2: 1% Soya oil, 0.5% fish oil, 1.5% bypass fat rich in omega 3. SAGPI3: 2.5% Soya oil, 0.5% fish oil. A source of bypass fat (GSP) was also used. The results were processed using pre-planned test comparisons through the PROC MIXED-SAS.The methane production in vitro decreased (p<0.05), while the dry matter digestibility increased (p<0.05) 24 and 48 hours after wild sunflower was include and / or AGPI or both into the mixtures. In the molar ratio of AGV (%), acetic acid showed an increased presence. The inclusion of forage like wild sunflower and sources of AGPI supplementation in cattle, could be a strategy to reduce methane emissions without causing a detriment to the ruminal fermentation.